From historical responsibility to carbon neutrality: A country classification - Dawud Ansari; Wassim Brahim; Franziska Holz; Claudia Kemfert (DIW Weekly Report, 2022)
The COP27 (United Nations Climate Change Conference) in November 2022 once again highlighted the fact that countries are starting from different positions when it comes to emissions and climate policy. This Weekly Report classifies countries into representative profiles based on their past, current, and planned future climate impact. There is a high degree of diversity between the profiles; they are not determined by geographical factors, but rather by economic patterns and policy decisions. This also applies to European Union member states: Levels of past CO2 emissions vary, and some countries have no domestic carbon neutrality. Globally, most countries have not contributed to cumulative emissions but also have no plans to become carbon neutral.
Keywords: Q54; F5; Q4; C38; 330; climate policy; hierarchical clustering; emission profiles; net zero